Pengaruh Gaya Hidup, Lingkungan Fisik, dan Persepsi Harga terhadap Loyalitas Pelanggan Lottemart - Damar Samintullah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
Retail business is a form of business that is increasingly popular among the public. Traditional retail business began to develop into a retail business that is processed with a more modern system. One of the retail businesses in Indonesia is Lotte Mart. Retail business in Indonesia continues to grow so that market competition emerges to increase customer loyalty. This study was conducted to determine the effect of lifestyle, physical environment, and price perception on customer loyalty. The population determined in this study are Lotte Mart customers who are in Surabaya City and Sidoarjo Regency. Researchers get 100 respondents obtained by purposive sampling technique. The data obtained through the questionnaire responses will be analyzed using multiple linear regression. The results of the study show that lifestyle has an influence on the formation of customer loyalty. In addition, customer loyalty is also influenced by the physical environment. Price perception has been shown to have a significant effect on customer loyalty.